The function of comparative fiqh in harmonizing differences among mazhabs in the contemporary era - Zulkefli, Muhammad Hamiz; Zakaria, Mohammad Ikram; Wan Zulkurnain, Wan Muhammad Nasrul Haq; Azlan, Muhammad Syauqi; Zairi, Muhammad Zarul Iman (2025)
Islamic jurisprudence fiqh has historically been characterized by a rich diversity of interpretations and methodologies, leading to the establishment of various islamic schools (schools of thought) such as Hanafi, Maliki, Shafi‘i, and Hanbali. While this plurality reflects the dynamic nature of Islamic legal thought, it has also posed challenges in achieving unity among Muslims, especially in addressing contemporary issues that transcend traditional boundaries. In the modern era, marked by rapid globalization, technological advancements, and complex socio-political dynamics, the need for a cohesive and adaptable Islamic legal framework has become increasingly evident. Comparative fiqh emerges as a vital tool in this context, facilitating the harmonization of differences among islamic schools by systematically analyzing and synthesizing diverse juristic opinions. The adoption of comparative fiqh methodologies enables scholars to navigate complex legal challenges by drawing upon the collective wisdom of various islamic schools. This approach not only preserves the core principles of Shariah but also promotes relevance, harmony, ethical guidance, and adaptability in addressing contemporary issues. By embracing a dynamic and inclusive perspective, comparative fiqh fosters consensus and community empowerment, ensuring that Islamic law remains responsive to the multifaceted issues of the modern world. (Saeed, 2023) Furthermore, the integration of comparative fiqh into Islamic jurisprudence encourages interdisciplinary engagement, bridging the gap between traditional legal thought and contemporary societal needs. These steps is crucial in dealing with modern legal issues such as bioethics, cyber law, global financial regulation, and environmental challenges, paving the way for productive dialogue between Islamic legal traditions and modern legal systems. (NurFaidah, 2024) Comparative fiqh serves as an indispensable mechanism for harmonizing differences among islamic schools, promoting unity, and enhancing the adaptability of Islamic law in the contemporary era. By fostering a deeper understanding of diverse perspectives and promoting harmonious coexistence among different schools of thought, comparative fiqh ensures that Islamic jurisprudence remains a living tradition, capable of guiding Muslims through the complexities of the modern world. (Saeed, 2023)